How Are Brain Fog Symptoms Related to Diet, Sleep, Mood and Gastrointestinal Health? A Cross-Sectional Study - Canan Altinsoy; Derya Dikmen (Medicina)
Background and Objectives: Brain fog, characterized by cognitive difficulties such as memory impairment, lack of focus, and mental fatigue, is a common symptom reported during recovery from COVID-19, particularly in long COVID cases. This study explores potential triggers such as sleep quality, mood, and gastrointestinal health and examines the link between adherence to the MIND diet and brain fog severity. Materials and Methods: A cross-sectional study was conducted between 1 July and 15 December 2022. The questionnaire assessed brain fog symptoms, dietary habits, sleep quality, mood, and gastrointestinal symptoms. Linear regression analysis examined the relationships between brain fog symptoms, demographic factors, sleep quality, MIND diet adherence, and gastrointestinal symptoms. Results: Brain Fog Scale (BFS) scores were significantly higher in individuals who had COVID-19 (p < 0.05) and even higher in those with reinfection. Women had higher BFS and Brain Fog Severity Score (BFSS), MIND Diet, The Gastrointestinal Symptom Rating Scale (GSRS), Brief Mood Introspection Scale (BMIS) Pleasant-Unpleasant scores (p < 0.05). BFS and BFSS were positively correlated with GSRS (p < 0.05), while no correlation was found with MIND diet adherence. A negative correlation was observed between BFS and Sleep Quality Scale (SQS) (p < 0.05), but this was not significant in regression (p = 0.367). GSRS, Pleasant–Unpleasant Dimension, and Arousal–Calm Dimension were significant predictors of BFS (R = 0.599, R2 = 0.358, p < 0.01). Conclusions: This study identifies being female as a risk factor for brain fog symptoms, with women reporting higher BFS and BFSS scores. While sleep quality showed a negative correlation with brain fog symptoms, this relationship was not significant in the regression model, suggesting that other factors, such as mood and gastrointestinal symptoms, may play a more dominant role. However, adherence to the MIND diet showed no significant relationship with brain fog symptoms. These findings suggest that addressing mood and gastrointestinal health may be key to managing brain fog in long COVID.